Strategies to Improve Education Quality at Junior High Schools - Puspita, Dian Grace; Sugiyono, Sugiyono (KnE Social Sciences, 2021)
This study aimed to introduce education practitioners and the general public to the strategies that schools have undertaken to improve the quality of education. This research used qualitative methods to explore existing phenomena. The research was conducted at one of the junior high schools in South Sulawesi, Indonesia. The data were collected through semi-structured interviews whose questions were developed after being in the field. The data were processed using qualitative data analysis techniques. Source triangulation was carried out with three teachers. The results showed that there were strategies that were considered effective in improving the quality of education. This quality improvement was indicated by the good student output and the trust of the community who considered the school to be one of their favorite schools in the area; through this quality improvement, the school became an example for others. Some of the strategies that were considered effective were implementing student-centered learning, increasing the number of high achieving new student admissions, strengthening human resources, providing educational rewards, and learning outside the classroom. Keywords: junior high school, education quality improvement